Thermal shock and fatigue behavior of pressureless sintered Al2O3âSiO2âZrO2 composites - Mebrahitom Asmelash, G. (Tsinghua University, 2015)
The thermal shock and fatigue behavior of pressureless sintered Al2O3âSiO2âZrO2 (ASZ) composites was studied. The influence of the thermal shock and fatigue on the strengthening response of ASZ has been investigated by measuring the strength retention and microstructural changes. The magnitude of the flexural strength and fracture of the ASZ has been compared with that of the monolithic Al2O3 (A) and Al2O3âZrO2 (AZ) composites under the same experimental conditions. Results indicated that the ASZ composites possess the highest resistance against thermal shock and fatigue, in comparison with A and AZ. The improvements were attributed to the enhancement in the fracture toughness of ASZ and the presence of multi-phase reinforcement. Â© 2015, The Author(s).